Experimental treatment of gastrointestinal bleeding with endoscopic high-frequency welding bipolar electrocoagulation. - Oparin, S. O.; Dyadyk, O. O.; Feleshtinsky, J. P.; Sorokin, B. V.; Kozlova, K. S.; Lutsenko, D. V.; Gruzinskiy, O. V. (Морфологія / Morphologia / Morfologìâ, 2018)
Background. Problem of treatment of gastrointestinal bleeding remains relevant. According to the Center of Medical Statistics of the Ukraine Health Ministry - total mortality of gastrointestinal bleeding in Ukraine is 5, 87%. In 2017, 18968 patients were hospitalized, of which 35, 56% with late hospitalization (> 24 hours). Mortality of gastrointestinal bleeding in Ukraine is 5, 87%, in Kiev - 7, 42%. Postoperative mortality in Ukraine is 5,15%, late hospitalization (>24h) — 7,86%; in Kyiv - 3,33%, late hospitalization — 6,32%. Endoscopic hemostasis reduces both general and postoperative mortality 3-4 times. There are a number of methods for endoscopic hemostasis: chemical (Caproferr, Infuzol), injectable (Epinephrine 1:20, Terlipressin), monopolar coagulation, argonoplasmic coagulation, laser coagulation, and clapping. Objective. We have proposed endoscopic high-frequency welding bipolar coagulation with a probe (Patented No. 115147, Application number u201608620 dated 10.04.17), which is carried out through the instrumental channel of the endoscope to the bleeding site. Methods. Welding of the vessel is provided by the high-frequency bipolar apparatus EK-300 M1. In order to evaluate the effectiveness of our method we conducted an experiment on pigs with morphological verification of the vessel's condition. We used two different probes for high-frequency welding bipolar coagulation, connected to the EK-300 M1 for welding bleeding vessel. Results. After coagulation visually we could see that bleeding was stopped in all cases. Morphologically was found that for stopping bleeding of vessels up to 1mm in diameter the most effective is the use of a probe 1 with an exposure time of 15s, for vessels more than 1mm is effective to use a probe 2 with an exposure time of 30s. Conclusion. Taking into account the results of our study and disadvantages of already existing methods, high-frequency welding bipolar electrocoagulation has its own advantages (superficial effect on tissue, good coagulation effect with bleeding vessels 2-3mm and more, can be used in patients with artificial pacemaker), therefore it is new expedient and justified method of endoscopic stopping of bleeding.